Deep-Water Ediacaran Fossils from Northwestern Canada: Taphonomy, Ecology, and Evolution. (March 2014) - Narbonne, Guy M.; Laflamme, Marc; Trusler, Peter W.; Dalrymple, Robert W.; Greentree, Carolyn
Abstract : Impressions of soft-bodied Ediacaran megafossils are common in deep-water slope deposits of the June beds at Sekwi Brook in the Mackenzie Mountains of NW Canada. Two taphonomic assemblages can be recognized. Soles of turbidite beds contain numerous impressions of simple ( Aspidella ) and tentaculate ( Hiemalora, Eoporpita ) discs. A specimen of the frond Primocandelabrum is attached to an Aspidella -like holdfast, but most holdfast discs lack any impressions of the leafy fronds to which they were attached, reflecting Fermeuse-style preservation of the basal level of the community. Epifaunal fronds ( Beothukis, Charnia, Charniodiscus ) and benthic recliners ( Fractofusus ) were most commonly preserved intrastratally on horizontal parting surfaces within turbidite and contourite beds, reflecting a deep-water example of Nama-style preservation of higher levels in the community. A well-preserved specimen of Namalia significantly extends the known age and environmental range of erniettomorphs into deep-water aphotic settings. Infaunal bilaterian burrows are absent from the June beds despite favorable beds for their preservation. The June beds assemblage is broadly similar in age and environment to deep-water Avalonian assemblages in Newfoundland and England, and like them contains mainly rangeomorph and arboreomorph fossils and apparently lacks dickinsoniomorphs and other clades typical of younger and shallower Ediacaran assemblages. Fossil data presently available imply that the classically deep- and shallow-water taxa of the Ediacara biota had different evolutionary origins and histories, with sessile rangeomorphs and arboreomorphs appearing in deep-water settings approximately 580 million years ago and spreading into shallow-water settings by 555 Ma but dickinsoniomorphs and other iconic clades restricted to shallow-water settings from their first known appearance at 555 Ma until their disappearance prior to the end of the Ediacaran.